PENGARUH STATUS SOSIAL EKONOMI RUMAH TANGGA DAN LITERASI EKONOMI TERHADAP PERILAKU KONSUMTIF SISWA - Nurul Lailiya; Sunanik Sunanik (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2019)
The purpose of this study was (1) to determine the effect of household socioeconomic status on students' consumptive behavior, (2) to determine the effect of economic literacy on students' consumptive behavior, (3) to determine the effect of household socioeconomic status and economic literacy on students' consumptive behavior. This research method is quantitative research. The sample in this study were 74 students of X students of SMAN 1 Kampak. The technique used in data collection uses a questionnaire to obtain data on household socioeconomic status (X1) and consumptive behavior (Y), while the test is to obtain data on students' economic literacy values (X2). The results of this study indicate that (1) there is a significant influence between household socioeconomic status on student consumptive behavior, (2) there is a significant influence between economic literacy on students' consumptive behavior, (3) there is a significant influence between household socioeconomic status and literacy economics on student consumptive behavior.